Artificial intelligence as an educational tool to improve teaching practice in initial education (project execution) - Briceño Matheus, Vanessa Alexandra (2025)
Artificial Intelligence (AI) is being incorporated into the educational process and teaching work with the aim of improving the quality of the teaching-learning process. The general purpose is to apply artificial intelligence as an educational tool to improve teaching practice in early education specifically in the “Niño Simón” Early Education Center, located in the Jalisco parish, Motatán municipality of Trujillo state. For this reason, a diagnosis was developed together with the social actors, building the plan to approach the group, which made it possible to highlight the lack of technological activities among the existing problems. Methodologically, Participatory Action Research (PAR) is presented adopting the model proposed by Kemmis and Mctaggart (2007), consisting of four fundamental phases represented in planning, action, observation and reflection. To collect information, the interview technique, brainstorming, nominal vote, problem tree and solutions are used.